2003
DOI: 10.1021/jm030223a
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Molecular Requirements for the Selective Delivery of Polyamine Conjugates into Cells Containing Active Polyamine Transporters

Abstract: Several N(1)-substituted polyamines containing various spacer units between nitrogen centers were synthesized as their respective HCl salts. The N(1)-substituents included benzyl, naphthalen-1-ylmethyl, anthracen-9-ylmethyl, and pyren-1-ylmethyl. The polyamine spacer units ranged from generic (4,4-triamine, 4,3-triamine, and diaminooctane) spacers to more exotic [2-(ethoxy)ethanoxy-containing diamine, hydroxylated 4,3-triamine, and cyclohexylene-containing triamine] spacers. Two control compounds were also eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 52 publications
5
159
0
1
Order By: Relevance
“…The inhibition of placental polyamine synthesis is related to decreased placental size and lower fetal growth . Polyamines are organic compounds that are derived from ornithine by the arginase pathway, resulting in the synthesis of putrescine, spermidine and spermine (Lehninger et al, 1993;Wang et al, 2003). However, the polyamine synthesis in the porcine placenta is dependent on the conversion of arginine into ornithine and proline via the arginase pathway in other maternal tissues, as arginase activity is not detected in the maternal placenta (Wu et al, 2006).…”
Section: Sow Nutrition As An Opportunity To Improve Within-litter Unimentioning
confidence: 99%
“…The inhibition of placental polyamine synthesis is related to decreased placental size and lower fetal growth . Polyamines are organic compounds that are derived from ornithine by the arginase pathway, resulting in the synthesis of putrescine, spermidine and spermine (Lehninger et al, 1993;Wang et al, 2003). However, the polyamine synthesis in the porcine placenta is dependent on the conversion of arginine into ornithine and proline via the arginase pathway in other maternal tissues, as arginase activity is not detected in the maternal placenta (Wu et al, 2006).…”
Section: Sow Nutrition As An Opportunity To Improve Within-litter Unimentioning
confidence: 99%
“…All exhibit similar function -high water solubility and rapid entry into cells -but they differ structurally in many significant respects except for the key conserved oligoguanidinium array. In addition to peptides, peptoids, and oligocarbamates, many other types of molecular transporters have been identified that cover a range of structural classes, including polyamines [5,6], polysaccharides During the past decade, many significant and exciting advances have been reported from our and other laboratories related to the mechanisms of uptake of GRTs and especially to their use in mediating cell and tissue uptake. An octaarginine transporter linked to Cyclosporin A has also been advanced to phase II clinical trials for dermatological applications [18] and a Tat 9-mer linked to a biologically active peptide cargo has been advanced clinically for the treatment of ischemia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many types of transporters have been reported in recent years including peptides (1)(2)(3)(4)(5), peptoids (6), polyamines (7,8), oligocarbamates (9), dendrimers (10,11), polysaccharides (12), steroids (13), cationic lipids (14,15), guanidinoglycosides (16), and even nanotubes (17). These transporters operate through a variety of mechanisms and some through multiple mechanisms depending on cell type, cargo, and other variables (5,(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%